Cyber-Resilience-Based Integrated Early Warning and Earthquake Response Information System Model: A Simulative Evaluation of Centralized and Distributed Configurations to Support Non-Military National Defenses - Mohammad Rayhan Syahman; Bambang Suharjo; H.A. Danang Rimbawa (Formosa Journal of Computer and Information Science, 2026)
This research designs and validates an integrated early warning and earthquake response information system model that places cyber-resilience as a built-in architectural property. The method used is Design Science Research with the model operationalized into an agent-based simulation on NetLogo, using a 2×2 factorial design (centralized vs. distributed configuration; earthquake vs. earthquake scenario accompanied by cyberattack) as many as 200 Monte Carlo replications per cell and latency calibration from real data of 39 BMKG earthquake events (average 165.3 seconds; SD 29 seconds). The results show that interoperability is fully maintained (100%) on all conditions. In dual interference, distributed configurations detected faster (MTTD 34 vs. 41 ticks), recovered faster (MTTR 110 vs. 140 ticks), maintained 100% common operating picture delivery success (vs. 74.21%), maintained higher integrity (71.53% vs. 54.11%), and limited blast radius to 66.67% (vs. 100%), with the controlled consequence of lower aggregate availability (77.08% vs. 90.47%).